The furculae of the dromaeosaurid dinosaur Dakotaraptor steini are trionychid turtle entoplastra - Arbour,Victoria M.; Zanno,Lindsay E.; Larson,Derek W.; Evans,David C.; Sues,Hans-Dieter (PeerJ, 2016)
Dakotaraptor steini is a recently described dromaeosaurid dinosaur from the Upper Cretaceous (Maastrichtian) Hell Creek Formation of South Dakota. Included within the D. steini hypodigm are three elements originally identified as furculae, one of which was made part of the holotype specimen. We show that the elements described as D. steini ‘furculae’ are not theropod dinosaur furculae, but are rather trionychid turtle entoplastra referable to cf. Axestemys splendida. The hypodigm of D. steini should be adjusted accordingly.
Keywords: Trionychidae; Dromaeosauridae; Theropoda; Testudines; Axestemys; Cretaceous; Maastrichtian; Hell Creek Formation; South Dakota